Land sparing versus land sharing: Moving forward - Joern Fischer; David J. Abson; Van Butsic; M. Jahi Chappell; Johan Ekroos; Jan Hanspach; Tobias Kuemmerle; Henrik G. Smith; Henrik von Wehrden (Conservation Letters, 2014)
To address the challenges of biodiversity conservation and commodity production, a framework has been proposed that distinguishes between the integration (“land sharing”) and separation (“land sparing”) of conservation and production. Controversy has arisen around this framework partly because many scholars have focused specifically on food production rather than more encompassing notions such as land scarcity or food security. Controversy further surrounds the practical value of partial trade-off analyses, the ways in which biodiversity should be quantified, and a series of scale effects that are not readily accounted for. We see key priorities for the future in (1) addressing these issues when using the existing framework, and (2) developing alternative, holistic ways to conceptualise challenges related to food, biodiversity, and land scarcity.
Keywords: 330; agroecological intensification; agroecology; food security; food sovereignty; land scarcity; matrix; sustainable intensification; wildlife-friendly farming